Partial replacement of inorganic N fertilizer by using humic acid, compost enriched with actinomyces and Spirulina platensis algae in strawberry cv. Festival - El- Shall, Z. S. A. (2012)
During 2009/2010 and 2010/2011 seasons, the possibility of replacing 25 to 75 % of inorganic N fertilizer in strawberry cv. Festival by using humic acid at 3 kg/ fed. compost enriched with actinomyces at 4 ton/fed. and Spirulina platensis algae at 3 L/ fed. was investigated. Results reveal that decreasing percentages of inorganic N from 100 to 50 % out of the suitable N rate accompanied with the application of humic acid, compost enriched with actinomyces or Spirulina platensis algae resulted in major promotion on growth, diameter and weight of fruit, yield as well as chemical characteristics of the fruits. Application of inorganic N combined with compost enriched with actinomyces was preferable than using mineral N plus humic acid in promoting yield quantitively and qualitatively.
Includes reference.
Summary in Arabic.
1
Keywords: Strawberries -- Fertilizers; Strawberries -- Varieties; Actinomyces; Compost; Humic acid; Nitrogen fertilizers; Spirulina platensis